A modified current collector for a sodium battery without negative electrode and its preparation method and application
By constructing a nitrogen-doped carbon coating with high content of N-5 and N-6 type doped nitrogen on the surface of the current collector of the negative-node sodium battery, the problem of low binding energy of the current collector and Na+ is solved, and the electrochemical performance and cyclic stability of the battery are improved.
Patent Information
- Application Number
- CN202510034637.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-01-09
AI Technical Summary
In existing negative electrode-free sodium batteries, the commonly used metal current collector has a low binding energy with Na+, resulting in uneven nucleation and growth of sodium on the surface of the current collector, causing the formation of dead sodium and dendrites, and reducing the battery's Coulomb efficiency and cycling stability.
By constructing a nitrogen-doped carbon coating rich in N-5 and N-6-type doped nitrogen on the surface of the current collector, the sodium-philic performance of the current collector is improved, the nucleation overpotential of the sodium metal is reduced, and the reversibility of the sodium deposition/stripping reaction is improved.
The electrochemical performance of the negative electrode-free sodium battery is significantly improved, including Coulomb efficiency and cycle stability, extends the cycle life of the battery and reduces the generation of dead sodium.
Smart Images

Figure CN119447322B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode-free sodium metal batteries, and in particular to a modified current collector for a negative electrode-free sodium battery, and a preparation method and application thereof. Background Art
[0002] Although lithium batteries have been widely used in portable electronic devices, electric vehicles, and large-scale energy storage, the limited lithium resources (0.0017 wt% in the earth's crust) and the drastic fluctuations in lithium prices have caused concerns about the sustainable development of lithium batteries. Therefore, sodium batteries, which are more abundant in resources (about 2.74 wt% in the earth's crust) and have lower manufacturing costs, have begun to attract widespread attention. Since the metallic sodium anode can provide extremely high theoretical specific capacity (1166 mAh / g) and low redox potential (-2.71 V vs standard hydrogen electrode), sodium metal batteries are considered to be the best choice for building high energy density sodium batteries. However, the application of sodium metal anodes still faces many challenges. For example, the abuse of sodium metal anodes. Although an excessively high anode / cathode capacity ratio can extend the cycle life of the battery, it usually significantly reduces the capacity utilization and energy density of the sodium metal anode. In addition, the chemical activity of metallic sodium is extremely high, and it is still difficult to prepare ultra-thin metallic sodium foil (<25 μm) on a large scale for practical use. Therefore, the concept of "anode-free sodium battery" has been proposed.
[0003] When charging a negative electrode-free sodium battery, Na + After being released from the positive electrode, it is directly deposited on the surface of the negative electrode current collector to form a sodium metal negative electrode in situ. This simplified battery structure not only effectively improves the energy density of the battery, but also avoids the safety issues caused by the direct use of sodium metal negative electrodes. However, commonly used metal current collectors (such as copper foil or aluminum foil) are not compatible with Na +The binding energy between them is low, which easily leads to uneven nucleation and growth of sodium on its surface, inducing the formation of dead sodium and dendrites, and ultimately leading to low coulombic efficiency of the battery, rapid capacity decay and short circuit. Therefore, people improve the electrochemical performance of negative electrode-free sodium metal batteries by constructing a sodium-philic coating on the surface of the current collector. For example, patent CN 117832512 A uses a high entropy metal nanoparticle / CNT mixture (HEA / CNT) as the current collector coating. On the one hand, sodium-philic high entropy nanoparticles can reduce the sodium metal nucleation overpotential and inhibit the growth of sodium dendrites; on the other hand, the introduction of CNTs can improve electronic conductivity and alleviate the volume change problem of sodium metal during the cycle process. However, the introduced metal particles not only increase the manufacturing cost, but also easily react with the electrolyte. Therefore, some studies (Huang B, Sun S, Wan J, et al. Advanced Science, 2023,10(11): 2206845, Zheng Z, Zeng X, Ye H, et al. ACS applied materials &interfaces, 2018, 10(36): 30417-30425.) directly use non-metallic elements to dope carbon materials as sodium-philic coatings to modify the current collector, such as nitrogen-doped carbon. In carbon materials, the types of doped nitrogen are mainly divided into: graphitized nitrogen (NQ), pyridinic nitrogen (N-5) and pyrrolic nitrogen (N-6). Compared with NQ-type doped nitrogen, N-6 and N-5-type doped nitrogen and Na + The binding ability is stronger, which is more conducive to promoting the uniform growth of metallic sodium on the coating surface. Therefore, how to increase the content of N-5 and N-6 type doped nitrogen becomes the key to improving the sodium affinity of nitrogen-doped carbon coatings.
[0004] Therefore, the present invention proposes a synthesis method for increasing the content of N-5 and N-6 type doped nitrogen in polypyrrole-derived nitrogen-doped carbon particles, and designs a modified current collector for a negative electrode-free sodium battery, and a preparation method and application thereof.
[0005] It should be noted that the above introduction to the technical background is only for the convenience of providing a clear and complete description of the technical solutions of the present application and for the convenience of understanding by those skilled in the art. It cannot be considered that the above technical solutions are well known to those skilled in the art simply because they are described in the background technology section of the present application. Summary of the invention
[0006] In view of the above-mentioned shortcomings that currently exist, the present invention provides a modified current collector for a negative electrode-free sodium battery, a preparation method thereof, and an application thereof. The modified current collector for a negative electrode-free sodium battery prepared by the present invention has a high relative content of N-6 and N-5 type doped nitrogen, thereby improving the sodium affinity of the nitrogen-doped coating, reducing the nucleation point of sodium metal, and improving the reversibility of the sodium deposition / stripping reaction, thereby improving the electrochemical performance (coulombic efficiency and cycle stability) of the negative electrode-free sodium battery.
[0007] In order to achieve the above object, the present invention provides a method for preparing a modified current collector for a negative electrode-free sodium battery, comprising the following steps:
[0008] S1, adding hydrochloric acid to anhydrous ethanol, stirring in an ice bath to obtain a uniform solution; adding a transition metal salt and an oxidant to the solution, after dissolving, adding pyrrole dropwise thereto, reacting in an ice bath, filtering, washing, and vacuum drying to obtain a polypyrrole precursor;
[0009] S2, placing the polypyrrole precursor in a porcelain ark, introducing an inert atmosphere, and then heating and performing heat preservation treatment to obtain N-doped carbon nanoparticles (NCP);
[0010] S3, mixing the N-doped carbon nanoparticles and a binder, adding N-methylpyrrolidone and mixing to form a uniform slurry; applying the slurry on a metal current collector with a scraper to form a coating, and after drying, obtaining a modified current collector for a negative electrode-free sodium battery.
[0011] The present invention, based on the preparation of polypyrrole, increases the relative content of N-6 and N-5 type doped nitrogen in polypyrrole-derived nitrogen-doped carbon nanoparticles by adding transition metal salts, thereby further improving the sodium affinity of the nitrogen-doped coating, reducing the nucleation point of sodium metal, and improving the reversibility of sodium deposition / stripping reactions, thereby improving the electrochemical performance of the negative electrode-free sodium battery.
[0012] According to one aspect of the present invention, the metal current collector is copper foil or aluminum foil.
[0013] According to one aspect of the present invention, in step S1, the concentration of the hydrochloric acid is 0.5-2 mol / L.
[0014] According to one aspect of the present invention, in step S1, the transition metal salt includes at least one of a transition metal salt, a sulfate, and a nitrate; the transition metal ion corresponding to the transition metal salt includes Sn 4+ , Fe 2+ , Fe 3+ 、Zn 2+ , Cu 2+ 、Co 2 + 、Co 3+ and Ni2+ At least one of .
[0015] According to one aspect of the present invention, in step S1, the oxidant is ammonium persulfate; the molar ratio of the transition metal salt to the ammonium persulfate is 5-100; and the molar ratio of the pyrrole to the ammonium persulfate is in the range of 0.2-5.
[0016] According to one aspect of the present invention, in step S1, the ice bath reaction time is 6 to 20 h; the vacuum drying temperature is 60 to 100 °C, and the time is 6 to 20 h.
[0017] According to one aspect of the present invention, in step S2, the temperature of the heat preservation treatment is 500-900°C, and the time is 1-6 hours; the inert atmosphere includes any one of nitrogen and argon.
[0018] It should be noted that the above heating rate is 2-15°C / min.
[0019] According to one aspect of the present invention, in step S3, the binder includes one or more of polyvinylidene fluoride, sodium carboxymethyl cellulose, sodium alginate, polytetrafluoroethylene, and polyacrylic acid; the mass ratio of the N-doped carbon nanoparticles to the binder is 7~8:1~3; preferably, the mass ratio of the N-doped carbon nanoparticles to the binder is 9:1, 8:2 or 7:3.
[0020] According to one aspect of the present invention, the scraper has a thickness of 10-50 μm.
[0021] Based on the same inventive concept, an embodiment of the present invention provides a modified current collector for a negative electrode-free sodium battery obtained by the above-mentioned preparation method.
[0022] Based on the same inventive concept, an embodiment of the present invention also provides an application of a modified current collector for a negative electrode-free sodium battery obtained by the above-mentioned preparation method in a negative electrode-free sodium battery.
[0023] According to one aspect of the present invention, the negative electrode-free sodium battery includes a modified negative electrode current collector, a separator, an electrolyte and a positive electrode current collector containing an active substance; the electrolyte is one or more of ethers and esters; the active substance is any one of polyanions, oxides, Prussian blue, and organic positive electrode materials.
[0024] Beneficial effects of the present invention:
[0025] (1) The present invention uses carbon nanoparticles doped with pyrrolic nitrogen (N-6) and pyridinic nitrogen (N-5) as a coating for the modified current collector. Compared with graphitized nitrogen (NQ) type doping, N-5 and N-6 type nitrogen doping sites have stronger binding ability with Na+. Increasing the content of N-5 and N-6 can improve the sodium affinity of the carbon substrate, which is beneficial to further reduce the nucleation overpotential of sodium metal and achieve uniform deposition of sodium metal. The application of this modified current collector in a negative electrode-free sodium metal battery can achieve higher coulombic efficiency and excellent electrochemical performance.
[0026] (2) Based on the traditional chemical oxidation method for preparing polypyrrole, the present invention introduces transition metal salts to achieve regulation of the nitrogen doping type in polypyrrole-derived nitrogen-doped carbon nanoparticles. This method is simple and safe and has high commercial potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The following are scanning electron microscope (SEM) images of the negative electrode current collectors of the embodiments and comparative examples of the present invention; wherein (a) is a SEM image of the current collector prepared in comparative example 2; (b) is a SEM image of the current collector prepared in example 1; (c) is a SEM image of the current collector prepared in example 2;
[0028] Figure 2 This is a high-resolution N 1s X-ray photoelectron spectroscopy (XPS) graph of the NCP prepared in Comparative Example 2 of the present invention;
[0029] Figure 3 This is a high-resolution N 1s XPS graph of the NCP prepared in Example 1 of the present invention;
[0030] Figure 4 This is a high-resolution N 1s XPS graph of the NCP prepared in Example 2 of the present invention;
[0031] Figure 5 The coulombic efficiency diagram of the sodium||current collector half-cell assembled with the negative electrode current collectors of Examples 1-2 of the present invention and Comparative Examples 1-2;
[0032] Figure 6 The cycle performance diagram of the negative electrode-free sodium battery assembled with the negative electrode current collectors of Examples 1 to 4 of the present invention and Comparative Examples 1 to 2. DETAILED DESCRIPTION
[0033] To make the present invention easier to understand, the present invention is further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. Unless otherwise defined, the professional terms used below are consistent with the meanings understood by professional and technical personnel in the field; unless otherwise specified, the raw materials and reagents involved in this article can be purchased from the market or prepared by known methods.
[0034] Example 1
[0035] A method for preparing a modified current collector for a negative electrode-free sodium battery comprises the following steps:
[0036] (1) Add 1 mol / L HCl solution (60 ml) to anhydrous ethanol (40 ml), stir in an ice bath to form a uniform solution, then add 20 mmol tin tetrachloride and 0.8 g oxidant ammonium persulfate, and continue stirring to dissolve. Add 0.4 ml pyrrole dropwise to the above solution and react in an ice bath for 8 h. After the reaction, the solution was filtered and the black product was washed three times with deionized water and ethanol respectively, and then dried in vacuum at 70 °C for 12 h to obtain a polypyrrole precursor.
[0037] (2) The polypyrrole precursor is placed in a porcelain ark, nitrogen is introduced, the temperature is increased (heating rate is 5°C / min) to 600°C and kept at this temperature for 3 h to obtain N-doped carbon nanoparticles (NCP).
[0038] (3) NCP and polyvinylidene fluoride were ground in a ratio of 9:1, and a certain amount of N-methylpyrrolidone was added to form a uniform slurry. The slurry was coated on a purchased commercial copper foil with a 50 μm scraper to form a coating. After drying, a negative electrode-free sodium battery modified current collector was obtained.
[0039] Example 2
[0040] The difference between this embodiment and embodiment 1 is that the amount of tin tetrachloride added is 50 mmol, and the other experimental parameters and conditions are consistent with those of embodiment 1.
[0041] Example 3
[0042] The difference between this embodiment and embodiment 2 is that the added transition metal salt is ferric chloride, and the other experimental parameters and conditions are consistent with those of embodiment 2.
[0043] Example 4
[0044] The difference between this embodiment and embodiment 2 is that the added transition metal salt is zinc dichloride, and the other experimental parameters and conditions are consistent with those of embodiment 2.
[0045] Comparative Example 1
[0046] The current collector of this comparative example is a commercial copper foil purchased.
[0047] Comparative Example 2
[0048] The difference between this comparative example and Example 1 is that the amount of tin tetrachloride added is 0 mmol, and the other experimental parameters and conditions are consistent with those of Example 1.
[0049] Performance testing and result analysis:
[0050] The negative electrode current collectors prepared in Examples 1-2 and Comparative Example 2 were subjected to SEM testing, and the results are as follows: Figure 1 As shown. Figure 1 It can be seen that there is no obvious difference in the morphology of the negative electrode current collectors of Examples 1 and 2, and both are highly agglomerated nanoparticles.
[0051] The negative electrode current collectors prepared in Examples 1-2 and Comparative Example 2 were subjected to XPS test, and the atomic ratios of the elements in the NCP prepared in different comparative examples and examples are shown in Table 1:
[0052] Table 1:
[0053]
[0054] Since tin tetrachloride was added during the preparation process, the NCP prepared in Example 1 and Example 2 contained Sn element, but the content was extremely low (<1%). At the same time, the N element content in the NCP prepared in Comparative Example 2, Example 1 and Example 2 was basically the same. In order to explore the type and relative content of doped nitrogen in the NCP prepared in Comparative Example 2, Example 1 and Example 2, the corresponding high-resolution N 1s XPS spectra were further processed for peak separation. The results are shown in Figure 2. Figures 2~4 As shown. Figures 2~4 It can be seen that the NCP prepared in Comparative Example 2, Example 1 and Example 2 all contain NQ (400.9 eV), N-6 (399.9 eV) and N-5 (398.2 eV). In the NCP prepared in Comparative Example 2, the contents of N-6 and N-5 are 15.0% and 33.8%, respectively. In the NCP prepared in Example 1, the contents of N-6 and N-5 are 36.5% and 33.9%, respectively. In the NCP prepared in Example 2, the contents of N-6 and N-5 are 32.6% and 38.8%. The above results show that the addition of tin tetrachloride is beneficial to increase the proportion of N-5 and N-6 type doped nitrogen in NCP, while N-5 and N-6 type doped nitrogen and Na +The binding ability is stronger than that of NQ type doped nitrogen, which is more conducive to the carbon substrate to Na + adsorption and subsequent nucleation-growth process.
[0055] The negative electrode current collectors prepared in Examples 1-2 and Comparative Examples 1-2 were used as working electrodes, and sodium was used as counter electrodes to conduct a cycle stability test of coulombic efficiency. The results are as follows: Figure 5 As shown. Figure 5 It can be seen that when commercial copper foil is used as the current collector, the coulombic efficiency fluctuates greatly, indicating that the reversibility of the deposition and stripping process of sodium metal is poor. At the same time, the coulombic efficiency of the current collector corresponding to the comparative example 2 of the NCP with high NQ-type doped nitrogen content also fluctuates greatly, indicating that its sodium affinity is poor. However, when the current collector of Example 1 or Example 2 is used, the coulombic efficiency is very stable, and the average coulombic efficiency reaches more than 99.8%, indicating that the reversibility of the sodium deposition / stripping reaction is high and the dead sodium generated is less, indicating that the modified negative electrode current collector of the present application has the potential to be used in negative electrode-free sodium metal batteries.
[0056] The negative electrode current collector prepared in Examples 1 to 4 and Comparative Examples 1 to 2 was used as the negative electrode, sodium iron pyrophosphate was used as the positive electrode, an ether electrolyte was used as the electrolyte, and a polypropylene film was used as the separator to assemble a negative electrode-free sodium metal battery, and its cycle stability was tested. The results are as follows: Figure 6 As shown. Figure 6 It can be seen that the modified current collectors in Examples 1 and 2 have a capacity retention rate of ~70% after 800 cycles at a current density of 200 mA / g, while the capacity retention rates of the current collectors in Comparative Examples 1 and 2 after 300 cycles are 5% and 51%, respectively. This result further confirms the application potential of the modified current collectors in Examples 1 to 4 in negative electrode-free sodium metal batteries.
[0057] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the art within the technical scope disclosed in the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A method for preparing a modified current collector for a negative electrode-free sodium battery, characterized in that: The following steps are involved: S1. Add hydrochloric acid to anhydrous ethanol and stir in an ice bath to obtain a uniform solution; A transition metal salt and an oxidant are added to the solution, and after dissolving, pyrrole is added dropwise thereto, and after ice bath reaction, the solution is filtered, washed, and vacuum dried to obtain a polypyrrole precursor; wherein the transition metal salt comprises at least one of chloride, sulfate, and nitrate; and the transition metal ion corresponding to the transition metal salt comprises Sn. 4+ 、Zn 2+ , Cu 2+ and Ni 2+ At least one of the following: the oxidant is ammonium persulfate; the molar ratio of the transition metal salt to the ammonium persulfate is 5 to 100; the molar ratio of the pyrrole to the ammonium persulfate is in the range of 0.2 to 5; S2, placing the polypyrrole precursor in a porcelain ark, introducing an inert atmosphere, then heating and performing a heat preservation treatment to obtain N-doped carbon nanoparticles; wherein the temperature of the heat preservation treatment is 500-900° C., and the time is 1-6 h; the inert atmosphere includes any one of nitrogen and argon; S3, mixing the N-doped carbon nanoparticles and a binder, adding N-methylpyrrolidone and mixing to form a uniform slurry; applying the slurry on a metal current collector with a scraper to form a coating, and after drying, obtaining a modified current collector for a negative electrode-free sodium battery.
2. The method for preparing a modified current collector for a negative electrode-free sodium battery according to claim 1, characterized in that: In step S1, the concentration of the hydrochloric acid is 0.5-2 mol / L.
3. The method for preparing a modified current collector for a negative electrode-free sodium battery according to claim 1, characterized in that: In step S1, the ice bath reaction time is 6 to 20 h; the vacuum drying temperature is 60 to 100 °C and the time is 6 to 20 h.
4. The method for preparing a modified current collector for a negative electrode-free sodium battery according to claim 1, characterized in that: In step S3, the binder includes one or more of polyvinylidene fluoride, sodium carboxymethyl cellulose, sodium alginate, polytetrafluoroethylene, and polyacrylic acid; the mass ratio of the N-doped carbon nanoparticles to the binder is 7-8:1-3; and the thickness of the scraper is 10-50 μm.
5. A modified current collector for a negative electrode-free sodium battery obtained by the preparation method according to any one of claims 1 to 4.
6. Use of a modified current collector for a negative electrode-free sodium battery obtained by the preparation method according to any one of claims 1 to 4 in a negative electrode-free sodium battery.
7. The use according to claim 6, characterized in that: The negative electrode-free sodium battery comprises a modified negative electrode current collector, a separator, an electrolyte and a positive electrode current collector containing an active substance; the electrolyte is one or more of ethers and esters; the active substance is any one of polyanions, oxides, Prussian blue, and organic positive electrode materials.
Citation Information
Patent Citations
Negative-electrode-free modified current collector for sodium battery as well as preparation method and application of negative-electrode-free modified current collector
CN117832512A
Nitrogen-doped amorphous carbon material as well as preparation method and application thereof
CN118026137A
Non-precious fuel cell catalysts comprising polyaniline
US20120088187A1